Overview of the Macedonian Policy Analysis Model (MAKPAM) - Tibor Hlédik; Sultanija Bojceva Terzijan; Biljana Jovanovic; Rilind Kabashi (National Bank of the Republic of Macedonia, 2016)
This paper describes the Macedonian Policy Analysis Model (MAKPAM), which is used at the National Bank of the Republic of Macedonia (NBRM) for medium term macroeconomic forecasting and policy analysis. The MAKPAM is a medium scale, New Keynesian gap model that incorporates the key characteristics of the Macedonian economy: a small open economy with a fixed exchange rate regime. This model outlines the transmission mechanism of the monetary policy in the Macedonian economy, and it helps to quantify the reaction of the economy to various shocks. Since 2008, the MAKPAM model has gradually become an important block of the macroeconomic forecasting system of the NBRM. The model is therefore an important analytic tool for supporting the monetary policy decision-making of the NBRM.
Keywords: C53; E47; E12; 330; New Keynesian; forecasting; monetary policy; Macedonia